2021
DOI: 10.3389/fonc.2021.629718
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics, Prognostic Value, and Immune Characteristics of m6A Regulators Identified in Head and Neck Squamous Cell Carcinoma

Abstract: N6-methyladenosine (m6A) plays crucial roles in a diverse range of physiological and pathological processes, and it is believed that it tremendously promotes neoplasia and progression. However, knowledge of the molecular characteristics of m6A modification, its prognostic value, and the infiltration of immune cell populations in head and neck squamous cell carcinoma (HNSCC) is still insufficient. Therefore, a pan-cancer genomic analysis was systematically performed here by examining m6A regulators at the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Further cellular functional experiments and in vivo experiments are needed to confirm the regulatory effect of N6‐methyladenosine RNA modification on GBM gene expression and to determine the correlation between N6‐methyladenosine modification and the origin and progression of GBM. In addition, the knockout or overexpression of key enzymes involved in N6‐methyladenosine modification may also be a good strategy and emerging direction for the study of N6‐methyladenosine methylation–mediated tumour cell responses 39‐42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further cellular functional experiments and in vivo experiments are needed to confirm the regulatory effect of N6‐methyladenosine RNA modification on GBM gene expression and to determine the correlation between N6‐methyladenosine modification and the origin and progression of GBM. In addition, the knockout or overexpression of key enzymes involved in N6‐methyladenosine modification may also be a good strategy and emerging direction for the study of N6‐methyladenosine methylation–mediated tumour cell responses 39‐42 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the knockout or overexpression of key enzymes involved in N6-methyladenosine modification may also be a good strategy and emerging direction for the study of N6-methyladenosine methylation-mediated tumour cell responses. [39][40][41][42]…”
Section: Discussionmentioning
confidence: 99%
“…There are over 655,000 new HNSCC cases per year, with over half a million deaths and ranking as the sixth most widespread and deadly cancer worldwide ( Ferlay et al, 2010 ). The important danger elements involve tobacco smoking, alcohol, and high-risk human papillomavirus infection ( Geng et al, 2021 ). Epstein–Barr virus infection is closely linked to nasopharyngeal carcinoma ( Hitt et al, 1989 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the aforementioned patients, nearly half of the patients showed increased expression of IGF2BP2, and the expression of the most common oncogene in HNSCC patients increased with higher levels of IGF2BP2. Similarly, Geng et al reported that IGF2BP2 is increased in HNSCC and serves as an m 6 A regulatory gene ( Geng et al, 2021 ). This shows that IGF2BP2 is closely related to the occurrence and development of HNSCC.…”
Section: Adenine-related Rna Modification Regulation In Head and Neck Squamous Cell Carcinomamentioning
confidence: 97%